Gendered spaces in party politics in Southern Africa: Progress and regress since Beijing 1995 - Onalenna Doo Selolwane (United Nations Research Institute for Social Development (UNRISD), 2006)
This paper was written as a contribution to the review of progress toward gender equality since the 1995 Beijing Conference with specific reference to the southern African region. It recognizes that in the African context, a review of this nature is necessarily also an assessment of how far institutions and processes of accountable governance, reestablished in the 1990s in most African states, are taking sufficient root to enable the realization of declared commitments to enhance the quality of life for any segment of the citizenry. The stocktaking focuses on political parties both as possible instruments and as sites of negotiated power, against a historical background where they have also been instruments of coercion and exclusion. They have thus embodied tension, as on the one hand products of repression, and on the other, symbols of a breakthrough to a future promising the African citizenry liberties and democratic rights coupled with improvements in material well-being. Therefore, a review of southern Africa's performance regarding progress towards gender equality cannot just be about the degree to which women are now represented in decision-making. Rather, the process of enhancing women's status is inseparable from the process of rebuilding democratic institutions and practices. This paper starts from the premise that the outcome of that institution-building is informed interactively by the nature of the struggles of the people or groups involved, in character, form and content. The question then is how the history of the southern African countries and the struggles waged therein have defined, and continue to shape, the type of institutions and the manner of political power-sharing and women's representation. Specifically, the paper examines what women's struggle for political space has added to the democratization process and the rebuilding of political parties in southern Africa. The southern African countries have been divided into groups that share certain historical similarities in order to examine how that history provided a context, and the obstacles that had to be overcome by women and other agencies in the process of building political institutions and negotiating political power. The groups are: * those countries that have maintained multiparty politics from the 1960s (Botswana and Mauritius) * those countries that replaced multiparty systems with single-party politics soon after independence and only reinstated them in the 1990s (Lesotho,Malawi, Mozambique, the Seychelles, the United Republic of Tanzania URT) and Zambia) * those countries that were the last to extend universal suffrage to all racial groups (Namibia and South Africa) * those countries that have regressed either right from independence or since, and have not yet embraced peaceful multiparty political systems (Angola, Swaziland, Democratic Republic of the Congo (DRC) and Zimbabwe).
Keywords: 330